A desinformação na esfera pública do estado constitucional e democrático de direito: uma análise sob o espaço cívico no contexto do estado brasileiro - Santos, Érico Antonio Pereira (2022)
This research is part of the line of Constitutional Jurisdiction and Democracy, its objective is to analyze the problems arising from the process of disinformation in the public sphere in the Constitutional and Democratic State of Law, specifically, in the case of the Brazilian State. To do so, it will be necessary to analyze the peculiar characteristics of the national public sphere, that is, the colonialist system, the slave regime, patriarchy and the permanence of political and economic oligarchies. Analyzing the main facts and social elements that structure contemporary Society, namely globalization, liberal market policies, State Sovereignty, fundamental rights and democracy. Drawing a parallel between these facts and social elements and the democratic, political and social crises, so that the critical points that link them can be identified. And in an ontological way, we study the transformations in the public sphere and its process of disinformation and manipulation of individuals. So that it is possible to examine whether the facts that give rise to the phenomenon of democratic recession, skepticism of democracy and the democratic deficit that plague Democratic States, especially Brazil, are linked to the process of disinformation in the public sphere. In this way, the social facts that transformed contemporary social relations will also be analyzed, such as the technological revolution, the advent of social networks, algorithms and Artificial Intelligence. And, finally, demonstrate that the process of disinformation and manipulation of the public sphere is directly related to the rise of autocratic populist movements, which in the post-truth era operate by disseminating fake news and hate speech and disrupting the Constitutional State. and Democratic Law, especially in the Brazilian case.